Development and performance testing of a positioning system for tank floor in-service inspection robots - Yewei KANG; Changfang WU; Zhenghong GUO (You-qi chuyun, 2025)
ObjectivePrecise positioning capability is essential for enabling tank floor in-service inspection robots to avoid obstacles, quantify defects, and achieve autonomous navigation. Accurately positioning these robots in metal tank environments demands not only rational positioning principles but also practical engineering practices. MethodsTwo acoustic emission transducers (beacons) carried by the robots are used to actively emit sound waves and multiple acoustic receiving transducers are mounted on the outer tank wall. This arrangement facilitates the positioning of tank floor inspection robots and the subsequent identification of defect locations by leveraging the hyperbolic positioning principle, which is based on the time difference of arrival (TDOA) of sound waves. The positioning beacons and transducers on the tank wall are designed to be explosion-proof, ensuring safe operation during positioning tasks in oil and gas environments. To mitigate the impact of empirical sound velocity methods on positioning accuracy, a sound velocity field estimation algorithm is employed to maintain rational sound velocity value ranges. Furthermore, to improve the accuracy of TDOA calculations, a generalized cross-correlation method is incorporated to estimate the time delay of the sound waves. To address the challenge of acoustic reverberation, which can lead to inaccuracies in time delay calculations, especially when a beacon is positioned close to the tank wall, an inertial measuring unit (IMU) is introduced. The integration of the IMU into the acoustic positioning system enhances the reliability of positioning results and improves the overall accuracy of robot positioning. ResultsThe results of verification through physical experiments and numerical simulations demonstrated that by utilizing a multiple-measure compensation mechanism, the developed positioning system achieved positional errors of no more than 10 cm and directional angle errors of less than 5° , thus meeting the requirements for precise robot positioning in tank environments. ConclusionThe positioning system based on TDOA of sound waves enables reliable and accurate positioning in cylindrical steel tank environments, supported by auxiliary sound velocity measurements and an IMU. This system provides robust support for the automation and intelligent functions of inspection robots.